Pemanfaatan Budaya Literasi di Sekolah Menengah Guna Meningkatkan Keterampilan Siswa - Siti Nurhidaya; Imas Juidah; Agus Nasihin; Yayah Kurniyah (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This study aims to explore the implementation of literacy culture at SMPN 2 Indramayu using a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. The findings indicate that the literacy program is carried out through various activities, such as reading sessions that foster critical thinking skills and enhance students’ confidence in expressing their ideas in public. However, several challenges remain, including the absence of reading corners in all classrooms and limited access to diverse reading materials. Despite these obstacles, the presence of a reading corner in the library and the active participation of students in literacy activities demonstrate the potential and effectiveness of the program. Student engagement in activities that develop critical thinking and public speaking skills serves as a positive indicator. To optimize literacy outcomes, this study recommends strengthening collaboration between teachers and students, as well as improving literacy resources and facilities in the school. With these steps, it is expected that the literacy culture at SMPN 2 Indramayu will continue to grow and positively impact students’ overall literacy skills.